Confessions of a shopaholic - Kinsella, Sophie (New York, N.Y. : Dell Publishing, 2001)
Young Rebecca Bloomwood, a financial magazine writer whose perpetual shopping has dug her into a huge debt hole, tries to turn her life around when she meets the desirable Luke Brandon.
"A Delta trade paperback.".
First published in the United Kingdom: Transworld, 2000.
Booklist.
Publisher's Weekly.
Adult
Keywords: Debt -- Fiction; Shopping -- Fiction; Young women -- Fiction; Bildungsromans; Debt -- Fiction; Humorous fiction; Shopping -- Fiction; Young women -- Fiction; London (England) -- Fiction; London (England) -- Fiction; Bildungsromane; Humorous stories